2014
DOI: 10.1149/06136.0015ecst
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Cellular Uptake and Toxicity of Engineered Nanomaterials

Abstract: Engineered Nanomaterials (ENs) such as silica, ceria and alumina nanoparticles have been extensively used in health care, energy and electronics. However, their toxicity and cellular uptake, which are strongly dependent on their physiochemical properties and on cell interaction, are largely unknown. The objective of this work is to study and quantify the cellular uptake of silica, ceria and alumina ENs. First, comprehensive characterization using DLS, zeta potential, BET, XRD, FTIR, Raman, SEM and TEM was done… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The results showed that supernatants (which may mainly contain additives and trace elements) of pre-CMP slurries showed no cytotoxicity compared to the controls. 10 It is evident from Table II that since the concentration of trace elements (additives) significantly decreased following CMP and pad rinse step, the toxicity observed at 1x dilution in the post-CMP slurries could only be due to silica NPs and not from trace elements or other additives.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The results showed that supernatants (which may mainly contain additives and trace elements) of pre-CMP slurries showed no cytotoxicity compared to the controls. 10 It is evident from Table II that since the concentration of trace elements (additives) significantly decreased following CMP and pad rinse step, the toxicity observed at 1x dilution in the post-CMP slurries could only be due to silica NPs and not from trace elements or other additives.…”
Section: Resultsmentioning
confidence: 96%
“…This is in good agreement with our previous results, where we showed that concentrated silica NPs (1x dilution) and not the other additives such as oxidizing and complexing agents, inhibitors and surfactants in the slurry are responsible for toxicity. 10 In this previous study, we investigated the effect of pre-CMP slurry supernatants on cellular toxicity. The supernatant were prepared by removing silica NPs from the pre-CMP slurry by centrifugation at 200,000g.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies by Shepard et al have demonstrated the presence of airborne silica and alumina NPs is a semiconductor plant around the CMP tool and NPs in waste water samples collected after waste filtration that are directed to the drain (1). There are a few reports (2,3) on the toxicity and uptake of CMP NPs that are mainly based on the pre-process NP slurries which report that silica NPs show toxicity. In our previous study on comparison of toxicity and uptake of pre-and post-CMP colloidal silica NPs, we reported that even though they have similar toxicity effects, the post-CMP NPs of colloidal silica showed higher uptake by A549 cells than that of pre-CMP NPs (4).…”
Section: Introduction and Objectivesmentioning
confidence: 99%